ANALISIS KEMAMPUAN PEMAHAMAN MATEMATIS TERHADAP PROKRASTINASI AKADEMIK SISWA DALAM MATEMATIKA - Riska Nurdiawan; Meri Siti Maryam; Lusi Lutfia; Trisatria Trisatria; Wahyudi Hermawan; Wahyu Hidayat (Departement of Mathematics Education, 2019)
This research aims to know the level of mathematical understanding ability against academic prokratinasi Junior High School students to find out of reduction of academicis a descriptive qualitative prokartinasi students in completing the task and a matter of mathematics. The method of this research is a descriptive qualitative, research done at the place of the junior high school cianjur classIX semester even. The research this belongs in a descriptive qualitative is attempting to describe the redution of academicprokartinasi students in working on and completing task and math problms. The population of this research this entire Junior class IX students in Cianjur. to obtain research data used instrument in the form of a test using SPSS application problem diagnostic and question form(questionner) prokartinasi academic students. the research result obtaineed conclusion : (1) the students skill level on the queston of the ability of understanding is still low,(2) academic prokartinasi students occured because of other activites to do,(3) students need to be given an action that could reduce academic prokartinasi students